PENGARUH PEMBERIAN KREDIT USAHA RAKYAT (KUR) DAN KOMERSIL TERHADAP PENINGKATAN PENDAPATAN USAHA MIKRO SAMPAI MENENGAH KE ATAS DI PT. BANK BRI UNIT SUMUR BATU TAHUN 2023 - Fadli Saputra; Tri Sulistyani (Journal of Research and Publication Innovation, 2025)
The purpose of this study was to determine the effect of Giving Kur (People's Business Credit) and Commercial on Increasing Micro to Medium Business Income at PT. Bank BRI Unit Sumur Batu Year 2023. The method used is a quantitative method used to analyze and know the Kur (People's Business Credit) and Commercial variables on Increasing Micro to Medium Business Income Up to Partially or Simultaneously. Data analysis using data instrument test, validity test, reliability test, classical assumption test, quantitative analysis, multiple linear regression test, hypothesis testing, and R² coefficient of determination analysis. The results of data analysis can be concluded that, Kur (People's Business Credit) has a positive and significant effect partially on increasing the income of micro to medium-sized businesses at PT. Bank BRI Sumur Batu Unit Year 2023, from the test results obtained t count > t table Kur (People's Business Credit (12. 125> 1.988) and has a significance of 0.000 < 0.05., Commercial variables have a positive and significant effect partially on increasing the income of micro to medium-sized businesses at PT. Bank BRI Unit Sumur Batu Year 2023, from the test results obtained Commercial obtained t count > t table (16.283 > 1.988) and has a significance of 0.000 < 0.05. and simultaneously shows that there is a positive and significant influence between Kur (People's Business Credit) and Commercial on Increasing Micro to Medium Business Income at PT. Bank BRI Unit Sumur Batu Year 2023. This is evidenced by the test obtained F_hitung value 822,208 > 3,156 F table with a significance value of 0.000 < 0.05. This can also be seen from the R Square of 0.659 or 65.9%, which means that the Kur (People's Business Credit) and Commercial variables have a contribution of 65.9% while 34.1% is influenced by other variables not explained in this study.